Stability study of sarpagandha ghana vati - A preliminary evaluation - Manohar Bajiya; Punam Aggarwal; R Galib; Pradeep Kumar Prajapati; Pramod R Yadav (Wolters Kluwer Medknow Publications, 2021)
Background: Shelf life is the time period until a product retains its therapeutic attributes and fit for use, consumption, or sale. Every product in this universe has definite shelf life. In Ayurveda texts, shelf life is referred as Saviryata avadhi that is defined as the time period during which the potency (Virya) of any drug remains unaffected. As per the regulations of Government of India, it is mandatory to mention shelf life on all marketed products on their labels. Sarpagandha ghana vati is an important formulation being used in Ayurvedic therapeutics; however, its shelf life is not reported till date. Aims and Objectives: The aim of this study was to evaluate the shelf life of Sarpagandha ghana vati through accelerated stability study. Materials and Methods: The formulation was prepared using authentic raw material and by following classical guidelines in the departmental laboratory. Shelf life was evaluated by analyzing changes in physicochemical profiles of the product after keeping it at specific temperature (40 ± 2°C) and relative humidity (75 ± 5%). Analysis was carried out at the intervals of 1, 3, and 6 months. Average 10% degradation time was calculated and extrapolated to find the shelf life as per the International Conference on Harmonization guidelines. Results and Conclusion: The shelf life of Sarpagandha ghana vati was found to be 16 months, which is higher than the average time period mentioned in the classical literature and lower than the time specified in the Gazette of India.